Religious Counseling to improve the self efficacy of lheukemia patients - Refnadi Refnadi (Education and Social Sciences Review, 2021)
Cancer is a potentially life-threatening disease. This can affect the patient's self-efficacy. The integration of religious counseling is expected to increase self efficacy in lheukemia patients. This qualitative research uses a case study approach with the subject of one lheukemia patient. Data mining in this research was carried out by observation, interview, then the data were analyzed by data reduction, data presentation and conclusion drawing. The results showed that individual counseling by integrating the religious greatness of God, sincerity, patience, repentance, and prayer made patients more enthusiastic in undergoing the treatment process and eager to undergo daily activities.